Pengaruh Konsentrasi Kolkisin Terhadap Fenotipe Tanaman Air Mata Pengantin (Antigonon leptopus) - Muhammad Akhlishil Ishlah; Muhammad Akhlish; Prameswari Permata Insani; Florentina Kusmiyati (Universitas Garut, 2022)
Antigonon leptopus is one of the flower plants that honey bees like because they contain nectar and pollen. The purpose of this study was to examine the effect of colchicine concentration on the phenotype of Antigonon leptopus. This study used a monofactor completely randomized design (CRD) with 7 replications. The treatment factors were 5 levels of colchicine concentration consisting of K0: 0 % (control), K1: 0,1 %, K2: 0,2 %, K3: 0,3 %, and K4: 0,4 %. The research data analysis used the F test and if it had a significant effect, it was continued with the DMRT test with level of α = 5 %. The results showed that soaking the seeds for 12 hours with colchicine was able to increase the diversity of phenotypes of Antigonon leptopus. The 0,1 % colchicine treatment had the best diversity in the parameters of tendril length, number of leaves, leaf area, number of flowers, flower diameter, flowering age and pollen weight, namely 76,8 cm, 34,6 cm, 61,5 cm2, 61,6 flowers, 3,0 cm, 44,4 days after planting, and 0,045 g. The 0,1 % colchicine treatment also showed a more concentrated flower color than the control. Colchicine treatment had no significant effect on the anther number parameter.